2022
DOI: 10.1097/md.0000000000030415
|View full text |Cite
|
Sign up to set email alerts
|

Effective anesthetic management with remimazolam and ketamine without muscle relaxants for parotidectomy in a patient with myotonic dystrophy: A case report

Abstract: Rationale: Patients with myotonic dystrophy (DM) are highly sensitive to anesthetics, muscle relaxants, and opioids, necessitating appropriate anesthetic management. Recently, remimazolam, an ultra-short-acting benzodiazepine, has been approved for use as a general anesthetic in Japan, and patients with DM have reportedly been treated with remimazolam. However, to the best of our knowledge, no study has reported on endotracheal intubation without the use of muscle relaxants under anesthetic management with rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nevertheless, a variety of drugs, such as rocuronium, benzodiazepines, and opiates, can be used before the induction of this general anesthesia as it helps prevent myoclonus ( 13 ). Recent studies indicate that remimazolam might be a useful drug in the future due to its circulatory stability and the possession of an antagonist ( 14 , 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a variety of drugs, such as rocuronium, benzodiazepines, and opiates, can be used before the induction of this general anesthesia as it helps prevent myoclonus ( 13 ). Recent studies indicate that remimazolam might be a useful drug in the future due to its circulatory stability and the possession of an antagonist ( 14 , 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…31 Others have reported either remimazolam monotherapy or remimazolam combined with ketamine or opioids to provide general anesthesia in patients with myotonic dystrophy or Duchenne muscular dystrophy. [32][33][34][35] Interestingly, flumazenil reversal was used in all cases, and the authors reported positive anesthetic and surgical outcomes. Other examples include remimazolam use in patients with mitochondrial-associated myopathy, encephalopathy, and stroke-like episodes that may otherwise be exacerbated by propofol.…”
Section: Remimazolam Use In Patients With Neurological Diseasesmentioning
confidence: 99%
“…A successful remifentanil and remimazolam total intravenous anesthetic was described in a patient with amyotrophic lateral sclerosis undergoing tracheostomy without neuromuscular blockade without adverse events 31 . Others have reported either remimazolam monotherapy or remimazolam combined with ketamine or opioids to provide general anesthesia in patients with myotonic dystrophy or Duchenne muscular dystrophy 32–35 . Interestingly, flumazenil reversal was used in all cases, and the authors reported positive anesthetic and surgical outcomes.…”
Section: Remimazolam Use In Patients With Neurological Diseasesmentioning
confidence: 99%